The study of suburbanization processes in the area of Gyöngyös District - Szűcs , Antónia; Koncz , Gábor (Studia Mundi – Economica, 2018)
In the last decades, suburbanization processes have also started in Hungary, as earlier in European metropolitan areas. Many of its effects were observed first and foremost in urban agglomeration of Budapest. As a consequence of the constant migration to the countryside, the suburban population increased. While the number of residents in the capital decreased. This process became more and more rapid in the 2000s in all the metropolitan agglomerations of the country.Our study focuses on the environment of a small-medium sized town, Gyöngyös. The phenomena related to residential suburbanization were investigated in the area of Gyöngyös district. It was explored what were the drivers of migration to rural settlements from 2001 to nowadays. The suburbanisation index was calculated for this purpose for each settlements of the district except the central town. Based on the results of a residential questionnaire it was analysed the composition and motivational characteristics of the population involved in suburbanization